An updated meta-analysis of the association between tumor necrosis factor-α -308G/A polymorphism and obstructive sleep apnea-hypopnea syndrome. - Anyuan Zhong (Public Library of Science (PLoS), 2014)
Background Several studies have reported that the tumor necrosis factor-α (TNF-α) -308G/A polymorphism is associated with susceptibility to obstructive sleep apnea-hypopnea syndrome (OSAHS). However, these results are controversial and conflicting. Objective To evaluate the association between TNF-α-308G/A and OSAHS risk by meta-analysis. Methods Electronic databases, including PubMed, Embase, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu, were searched to identify relevant studies. Data were extracted from the included studies. A model-free approach using odds ratio (OR), generalized odds ratio (ORG) and 95% confidence interval (CI) of the allele contrast to assess the association between the -308G/A polymorphism and OSAHS risk. Cumulative and recursive cumulative meta-analyses (CMA) were also carried out to investigate the trend and stability of effect sizes as evidence accumulated. Results Seven studies including 1369 OSAHS patients and 1064 controls were identified in this meta-analysis. Significant associations were derived from the variants of the allele contrast [(OR, 1.78; 95% CI, 1.45-2.18) or (ORG, 2.01; 95% CI, 1.27-3.19). CMA showed a trend of an association. Recursive CMA indicated that more evidence is needed to conclude on the status of significance. No significant publication bias was found. Conclusions Our meta-analysis suggested that the TNF-α-308G/A polymorphism contribute to the risk of OSAHS. Further studies with larger sample should be performed to confirm our findings.